Experiences of Danish Business Expatriates in Russia: Power Distance in Organizational Communication. Issue 4 (3rd July 2016) - Chudnovskaya, Elena V.; O'Hara, Laura S.
Abstract: Rapid globalization of business processes stimulates many companies to dispatch their employees – business expatriates – on overseas assignments. Russia differs markedly from many other cultures in terms of specific communication norms and rules. Understanding such differences in organizational life is crucial for the success of business expatriates working there. This study employs in-depth interviews with eight Danish business expatriates who worked in Russia and examines the differences between the Danes and the Russians in terms of communication characteristics related to Hofstede's cultural dimension power distance . This work enhances scholars' empirical knowledge of power distance, which has rarely been investigated qualitatively.